Origin of high thermal stability of amorphous Ge1Cu2Te3 alloy: A significant Cu-bonding reconfiguration modulated by Te lone-pair electrons for crystallization. (15th May 2015) - Chen, Nian-Ke; Li, Xian-Bin; Wang, Xue-Peng; Xia, Meng-Jiao; Xie, Sheng-Yi; Wang, Hai-Yu; Song, Zhitang; Zhang, Shengbai; Sun, Hong-Bo
Graphical abstract: Abstract: Ge1 Cu2 Te3 is an important candidate for high-temperature phase change memory due to the fine amorphous stability. Yet, the basic bonding chemistry for its high-temperature application is still not completely clear. In this work, a new bonding mechanism for its amorphous and crystalline phases is proposed and demonstrated by first-principles calculations. Compared to the tetrahedral environment distributed evenly in crystalline form, Cu atoms in the amorphous state tend to be accumulated as trigonal clusters. For the crystalline phase, a bonding configuration of nonequivalent sp 3 hybridization with Te lone-pair electrons is proposed without Cu d electron participation. In the amorphous phase, however, a significant bonding reconfiguration of Cu d electrons occurs due to the isolation of the Te lone-pair electrons. Therefore, the notable contrast in the Cu atomic and electronic structures between the crystalline and amorphous phases results in an obvious phase transition barrier for high-temperature storage. The mechanism presented in this study serves as a reference for other transition-metal alloyed phase-change materials.